Harnessing stakeholder knowledge for the collaborative development of Mobulid bycatch mitigation strategies in tuna fisheries. (9th June 2022) - Cronin, Melissa R; Croll, Donald A; Hall, Martin A; Lezama-Ochoa, Nerea; Lopez, Jon; Murua, Hilario; Murua, Jefferson; Restrepo, Victor; Rojas-Perea, Stefany; Stewart, Joshua D; Waldo, Jennifer L; Moreno, Gala
Abstract: Manta and devil rays (Mobulids) face several immediate threats, including incidental capture in industrial tropical tuna fisheries. As a result, efforts have emerged to avoid or mitigate Mobulid bycatch in these fisheries. However, many mitigation efforts fail to incorporate fisher expertise from the outset, potentially leading to interventions that are not viable. Here, we combine survey and focus group data to synthesize knowledge of Mobulid bycatch and mitigation ideas in Eastern Pacific Ocean purse seine fisheries. Primary obstacles for mitigating Mobulid bycatch, according to respondents, are: (1) an inability to sight Mobulids before capture, (2) the lack of specific equipment on board, and (3) the difficulty of releasing large individuals; we suggest that the latter two can be addressed by simple operational modifications. We also find that Mobulids are most likely to be sighted by fishers after capture, suggesting that this is an important time in the fishing operation for bycatch mitigation interventions that ensure Mobulids survive capture. To address this, we share creative ideas brought by fishers for avoidance of Mobulids. This study provides a model of how to incorporate stakeholder input in the design of bycatch technology in large-scale fisheries and could inform similar efforts around the world.